2019
DOI: 10.1186/s42269-019-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of heat shock proteins in maize (Zea mays L.)

Abstract: Background: Maize is one of the important cereal food crops in the world. High temperature stress causes adverse influence on plant growth. When plants are exposed to high temperatures, they produce heat shock proteins (HSPs), which may impart a generalized role in tolerance to heat stress. Proteome analysis was performed in plant to assess the changes in protein types and their expression levels under abiotic stress. The purpose of the study is to explore which proteins are involved in the response of the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Proteomics analysis of ethylene pre-treated tomato pollen by LC-MS/MS suggested that various proteins help in protecting pollen development and function through higher abundance of protein synthesis and upregulating stress protecting proteins that maintain cellular redox state under heat stress (Jegadeesan et al, 2018). Proteomics analysis by 2-DE technique allowed identification of important heat shock proteins viz., HSP26, HSP16.9, and unknown HSP/Chaperonin contributing to heat stress tolerance in maize (Abou-Deif et al, 2019). Considering contributory role of proteins adapting roots under heat stress, Valdes-Lopez et al (2016) reported the involvement of both up and down regulatory proteins contributing to heat tolerance in soybean root.…”
Section: Proteomicsmentioning
confidence: 99%
“…Proteomics analysis of ethylene pre-treated tomato pollen by LC-MS/MS suggested that various proteins help in protecting pollen development and function through higher abundance of protein synthesis and upregulating stress protecting proteins that maintain cellular redox state under heat stress (Jegadeesan et al, 2018). Proteomics analysis by 2-DE technique allowed identification of important heat shock proteins viz., HSP26, HSP16.9, and unknown HSP/Chaperonin contributing to heat stress tolerance in maize (Abou-Deif et al, 2019). Considering contributory role of proteins adapting roots under heat stress, Valdes-Lopez et al (2016) reported the involvement of both up and down regulatory proteins contributing to heat tolerance in soybean root.…”
Section: Proteomicsmentioning
confidence: 99%
“…In maize, as in Arabidopsis, heat shock activates the expression of both high and low molecular weight HSPs [ 3 , 43 , 44 , 45 , 46 ]. The proteins in maize plants produced in response to heat shock were identified through a proteome analysis and included such proteins as the ATPase beta subunit, HSP26, HSP16.9, and unknown HSP/chaperonin [ 47 , 48 ]. It was actually surprising to find that Hsp26, an early heat stress marker gene, and Hsp17.6 and Hsp18.2 were upregulated under the simulated field conditions when the temperatures were slowly ramped up [ 14 ].…”
Section: Heat Stress Response (Hsr) a Cytoplasmic Heat Stress Resmentioning
confidence: 99%
“…The top-five class consisted of a single organism process, biosynthetic process, response to stimulus, oxidation-reduction process, and response stress response. The response stress process sub-category is clustered genes that are regulated under stress [19]. The stimulus-response of an organism is indicated as a process that causes changes in cells activities, secretion, gene expression, enzyme production, and cellular responses.…”
Section: B Gene Ontologymentioning
confidence: 99%
“…Furthermore, HSPs divided into 3 clusters based on their molecular weight consisted of high molecular weight (80-114 kDa), HSP70 (69-71 kDa), and low molecular weight (15-30 kDa). HSPs were consisted of six structurally conserved distinct classes including HSP100, HSP90, HSP70, HSP60 (Chaperonins), small HSPs (sHSPs), and ubiquitin (8,5 kDa) [19]. Major HSPs were synthesized in eukaryotes [20].…”
Section: B Gene Ontologymentioning
confidence: 99%
See 1 more Smart Citation